Synthesis and characterization of polypropylene‐graft‐poly(l‐lactide) copolymers by CuAAC click chemistry. Issue 22 (12th September 2018) - Acik, Gokhan; Altinkok, Cagatay; Tasdelen, Mehmet Atilla
ABSTRACT: The syntheses of polypropylene‐ graft ‐poly(l ‐lactide) copolymers (PP‐ g ‐PLAs) via copper (I)‐catalyzed azide‐alkyne cycloaddition "click" reaction (CuAAC) using azide side‐chain functionalized polypropylene (PP‐N3 ) and alkyne end‐functionalized poly(l ‐lactide) (PLA‐Alkyne) were reported. The CuAAC was then applied to azide and different feeding ratios of alkyne functional polymers to give PP‐ g ‐PLAs that were characterized by FTIR, 1 H‐NMR, GPC, DSC, and WCA measurements. The CuAAC click reaction was achieved by two different feeding ratio (PP‐N3 :PLA‐Alkyne = 1:5 and 1:10) and thermal, biodegradable, and surface properties of obtained graft copolymers were investigated. The molar ratio of PLA were calculated as 72.7 (PP‐ g ‐PLA‐1) and 78.4% (PP‐ g ‐PLA‐2) by 1 H‐NMR spectroscopy. The water contact angle (WCA) values of PP‐ g ‐PLA‐1 (81 o ± 1.3) and PP‐ g ‐PLA‐2 (75 o ± 1.6) copolymers were compared with commercial chlorinated polypropylene (PP‐Cl) (90 o ± 1.0), suggesting a more hydrophilic nature of desired graft copolymers produced. Conversely, the enzymatic biodegradation studies revealed that the weight losses of graft copolymers were determined as 13.6 and 22.1%, which is about 4% for commercial PP‐Cl sample. Thus, it was clear that this simple and facile method was effective in promoting biodegradation of commercial polypropylene and attractive particularly for worldwide environmental remediation goals. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2595–2601 Abstract : Polypropylene‐ graft ‐poly(l ‐lactide) copolymers (PP‐ g ‐PLAs) were synthesized from commercially available chlorinated polypropylene via copper (I)‐catalyzed azide‐alkyne cycloaddition "click" reaction (CuAAC). Their chemical structures, thermal, surface, and biodegradation properties were investigated by spectral, chromatographic, thermal, contact angle analyses, and enzymatic degradation experiments.